Translation techniques of Indonesian children’s picture book: The Sacred Crocodile - Iin Inawati; Dian Savitri; Dian Rosawati Fitriani; Nita Listiyaningtyas (Teaching English as a Foreign Language Journal, 2022)
Translating a children's picture book is a challenging process. The focus of translating children's picture books is not only to transfer the meaning into the target language but also to guide the children to quickly understand the meaning of the sentences. Therefore, the translator must apply the appropriate sentence translation technique. This study aims to describe translation techniques used in translating Indonesian children's picture books into English. The data of this study are sentences taken from the Indonesian picture book "The Sacred Crocodile." The researchers used purposive sampling and a comparative method to analyze the data. The finding shows that translators use five translation techniques by Vinay and Darbelnet (1995) in translating sentences: literal translation, modulation, transposition, and equivalence. The literal translation is the most frequently used translation technique, followed by transposition. The literal translation is a technique by which the translator translates expressions word-for-word from SL into TL. The dominant use of literal translation indicates that the translator tried to make the sentences easily understood by children. For further study, the researcher may consider the psychological aspects and characteristics of the children in order to motivate the children to read an English story book.